Operation of a grid-connected AC microgrid in presence of plug-in hybrid electric vehicle, price, load and generation uncertainties - Singh A.; Maulik A.; Das D. (My University, 2025)
Integration of distributed generation, including renewable power sources, is becoming increasingly commonplace at the distribution level to address issues like depleting fossil fuel reserves and greenhouse gas emissions. Moreover, a shift from fossil fuel-based vehicles to electric vehicles is also becoming a global phenomenon. Variability and uncertainties of renewable sources and penetration of electric vehicles alter the existing load profile in a power system and pose a challenge to power system operation. An integrated optimal operating approach is proposed in this paper to reduce the cost of operation (while satisfying other steady-state performance requirements like voltage profile and line flow limits) of a microgrid with distributed generation and plug-in hybrid electric vehicle charging load. The impact of different charging schemes of plug-in hybrid electric vehicles on the system performance is also assessed. A group of measures (optimal scheduling of dispatchable sources and storage system, network reconfiguration) is implemented to improve system performance. Uncertainties of grid power price, renewable generation, load demand, plug-in hybrid electric vehicle charging load under different charging strategies are modeled using a probabilistic approach. The benefits of the proposed approach are demonstrated by simulation studies on a thirty-three node microgrid test system. © 2021 IEEE.